Pumping-induced reactivation of a pre-existing normal fault: insights from a centrifuge model test - Wan, Jiawei; Li, Bin; Gao, Yang; Tan, Chengxuan; Li, Zhuang (Frontiers in Earth Science, 2023)
Pumping-induced normal fault reactivation and the resultant ground fracture have been observed in faulted basins worldwide, but the process and mechanism are poorly understood thus far. In this study, we conducted centrifuge model tests to investigate and analyze these issues. Two simplified faulted models, Models 1 and 2, were developed based on an actual event that occurred in the Beijing Plain, China. Our model tests reproduced the pumping-induced normal fault reactivation, characterized by localized hanging wall subsidence with new fault scarp formation in the models. The monitoring results showed that water table decline drastically accelerated uneven subsidence. Although the deformation pattern did not respond to variations in the material properties of the hanging wall and footwall, the magnitude of the reactivated normal faulting was influenced. The maximum vertical offset in Model 2 was much larger than that in Model 1 due to a larger compression modulus in the hanging wall and footwall in Model 2. Furthermore, the reactivation mechanism was revealed based on Anderson's faulting theory. Normal faulting occurs once the maximum principal stress becomes vertical and the intermediate and minimum principal stresses become horizontal. Groundwater pumping increases the effective stress, leading to the addition of vertical stress and the resultant normal fault reactivation. Our findings provide a better understanding of human interactions with the Earth's surface and are helpful for mitigating faulting-caused disasters.